Hemophagocytic lymphohistiocytosis following an acute HIV infection, in a known immunosuppressed patient: A case report. (2022) - Beires, Francisca; Laranjinha, Joana; Pinho, Ana; Duarte, Frederico
Abstract: Background: Hemophagocytic lymphohistiocytosis (HLH) is a rare hyperinflammatory condition with a wide range of causes, being frequently associated with infections in adults. The association between HLH and acute HIV infection has been rarely described. Case presentation: A 62-year-old male, with a past medical history of Henoch-Schönlein purpura under immunosuppressive treatment, presented with a two-week history of fever, asthenia, anorexia, cough and purpuric rash. Initial blood tests showed pancytopenia, elevated C-reactive protein and renal failure. Microbiological investigations were negative, but persistent fever and pancytopenia led to HLH suspicion. This diagnosis was supported by hyperferritinemia, hypertriglyceridemia, high soluble-interleukin-2 receptor levels and hepatosplenomegaly, fulfilling 5/8 diagnostic criteria of the Histiocyte Society-2004. Further investigation revealed a positive HIV-1 antibody and the patient reported recent sexual risks, with TCD4 + lymphocytes below 100/mL and HIV-1 viremia above 10 million copies/mL, confirming an acute HIV infection. Antiretroviral therapy (ART) and glucocorticoids were started with full clinical recovery. Conclusion: HLH occurrence can be obscured by the features of a primary disease and can mimic other clinic conditions. In this patient, the prompt identification of an acute HIV infection as the cause of HLH allowed the early initiation of antiretroviral treatment and corticosteroids, with an efficient control of the viral replication and inflammatory response, preventing a potentially fatal evolution.